2012
DOI: 10.1016/j.actbio.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural manipulation of electrospun scaffolds for specific bending stiffness for heart valve tissue engineering

Abstract: Biodegradable thermoplastic elastomers are attractive for application in cardiovascular tissue construct development due to their amenability to a wide range of physical property tuning. For heart valve leaflets, while low flexural stiffness is a key design feature, control of this parameter has been largely neglected in the scaffold literature where electrospinning is being utilized. This study evaluated the effect of processing variables and secondary fiber populations on the microstructure, tensile and bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 41 publications
4
81
0
Order By: Relevance
“…non-linearity, anisotropy and elastic moduli [35]) and of out-of-plane behavior (e.g. bending stiffness [36]). At smaller scales (mesoscopic scale with a characteristic length of ~100 μm), various model predictions [2-4, 9, 12, 25, 28] can estimate fibers network kinematics and mechanics [37] and elucidate the effects of macroscopic deformations and micro architecture on cells/inclusions.…”
Section: -Introductionmentioning
confidence: 99%
“…non-linearity, anisotropy and elastic moduli [35]) and of out-of-plane behavior (e.g. bending stiffness [36]). At smaller scales (mesoscopic scale with a characteristic length of ~100 μm), various model predictions [2-4, 9, 12, 25, 28] can estimate fibers network kinematics and mechanics [37] and elucidate the effects of macroscopic deformations and micro architecture on cells/inclusions.…”
Section: -Introductionmentioning
confidence: 99%
“…Mechanical properties of biomaterials can be tuned by adjusting diverse parameters, such as crosslinking [19], material concentration [20,21], and architecture [22,23]. The mechanical properties of fiber-reinforced bio-composites are relatively easier to manipulate by adjusting their fiber fraction and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study of the same group of electrospun PEUU under variable conditions which modelled the effects of fiber orientation on the macro-mechanical properties of the scaffold, has shown that the high velocity electrospun scaffolds exhibited highly anisotropic mechanical properties closely resembling the native pulmonary heart valve leaflet [103]. Aiming to mimic the mechanical properties of a native pulmonary valve in both flexural and equi-biaxial tensile response, Amaroso et al studied the effect of microstructural features, that are important on the flexural behaviour of electrospun scaffolds, by introducing secondary electrospun fibers to the PEUU with simultaneous electrospinning [104]. It was noticed that mixed fiber constructs with higher modulus had higher bending and tensile moduli when secondary fibers were stiffer (PCL) than PEUU, whereas sacrificial fibers (PEO) within scaffolds were found to decrease overall construct modulus.…”
Section: Polyurethane-based Scaffoldsmentioning
confidence: 99%